2000
DOI: 10.1002/chin.200039256
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Stereoselective 1,3‐Dipolar Cycloadditions to Heterocyclic Compounds

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…More significantly we show that efficient dethreading of [n]semirotaxanes allows isolation of regioselectively pure 1,3-dis-ubstituted triazole compounds. To the best of our knowledge this is the only synthetic method which gives direct access to the 4-regioisomer of 1,3-triazole derivatives without the need for the separation of regioisomers 13,14 and should therefore be an attractive proposition in natural product synthesis.…”
mentioning
confidence: 99%
“…More significantly we show that efficient dethreading of [n]semirotaxanes allows isolation of regioselectively pure 1,3-dis-ubstituted triazole compounds. To the best of our knowledge this is the only synthetic method which gives direct access to the 4-regioisomer of 1,3-triazole derivatives without the need for the separation of regioisomers 13,14 and should therefore be an attractive proposition in natural product synthesis.…”
mentioning
confidence: 99%
“…Over the years, nitrones have become important building blocks in organic synthesis. [1][2][3][4][5][6][7][8][9][10] Nucleosides are generally defined as DNA or RNA subunits and consist of both a base moiety such as adenine, thymine, guanine, cytosine and uracil, and a sugar moiety such as D-ribose or 2-deoxy-D-ribose. 11 Many nucleoside analogues have been synthesized with modification of the base, sugar, and phosphate moieties.…”
Section: Introductionmentioning
confidence: 99%
“…1,3-Dipolar cycloaddition reactions are versatile organic transformations, used mainly for the synthesis of a variety of five-membered heterocyclic ring systems. In these reactions, the dipolarophile is normally an alkene/alkyne derivative or a heteroaromatic derivative. In an earlier study, George et al , have shown that bis(phenylazo)stilbene ( 1 ) reacts with acetylenic and olefinic dipolarophiles to give the corresponding 1:1 adducts (Scheme ), arising through a 1,3-dipolar type of cycloaddition.…”
Section: Introductionmentioning
confidence: 99%